Being cool : the work of Elmore Leonard - Rzepka, Charles J. (The Johns Hopkins University Press, 2013)
An in-depth look into the life and work of the man who defined "cool" for crime fiction, Elmore Leonard. Widely known as the crime fiction writer whose work led to the movies Get Shorty and Out of Sight, Leonard had a special knack for creating "cool" characters. In this book, the author looks at what makes the dope-dealers, bookies, grifters, financial advisors, talent agents, shady attorneys, hookers, models, and crooked cops of Leonard's world cool. They may be nefarious, but they are also confident, skilled, and composed. And they are good at what they do. Taking being cool as the highway through Leonard's life and works, the author finds plenty of byways to explore along the way. This book delineates the stages and patterns that characterize Leonard's creative evolution. Like jazz greats, he forged an individual writing style immediately recognizable for its voice and rhythm, including his characters' rat-a-tat recitations, curt backhands, and ragged trains of thought. The author draws on more than twelve hours of personal interviews with Leonard and applies what he learned to his close analysis of the writer's long life and prodigious output: 45 published novels, 39 published and unpublished short stories, and numerous essays written over the course of six decades. -- Provided by publisher.